3526 Healthy eating, physical activity, sleep and cognitive function in elderly population: Data from National Health and Nutrition Examination Survey 2011-2014. (27th March 2019) - Shaheen, Magda
Abstract : OBJECTIVES/SPECIFIC AIMS: To examine the relationship between healthy eating, physical activity (PA), sleep problem and hours of sleep and cognitive function among elderly population and the racial/ethnic differences in this relation. METHODS/STUDY POPULATION: We analyzed data from National Health and Nutrition Examination Survey 2014-2016 for 882 population 60 years and older. Cognitive status was measured by the Digit Symbol Substitution (DSS) exercise score and the Consortium to Establish a Registry for Alzheimer's Disease (CERAD) total score. Healthy eating index (HEI), PA, and sleep problem and hours of sleep were assessed by questionnaire. The association between cognitive function and HEI, PA, sleep problem and hours of sleep were assessed by linear regression after adjusting for age, gender, race/ethnicity, poverty level, lipid profile, fasting glucose level, alcohol, body mass index, stroke and education. Data were analyzed using Stata 14 considering design and sample weight and p<0.05 is statistically significant. RESULTS/ANTICIPATED RESULTS: CERAD total score was associated with HEI (Adjusted B = 0.07, 95% Confidence Interval (CI) = 0.01-0.13, p = 0.02) and not associated with physical activity or sleep problem or hours of sleep (p > 0.05). Animal fluency score was associated only with HEI (Adjusted B = 0.05, 95% CI = 0.01-0.09, p = 0.02). DDS score was not associated with HEI, PA, or sleep problem (p > 0.05) but associated with hours of sleep (p = 0.03). Stratified analysis by race/ethnicity showed that CERAD total score was associated with HEI only in White (Adjusted B = 0.08, 95% CI = 0.01-0.15, p = 0.02). DISCUSSION/SIGNIFICANCE OF IMPACT: CERAD total score was associated with HEI and not associated with PA or sleep problem. Promoting healthy eating is important for improving cognition in elderly population. Culturally sensitive and linguistically appropriate programs that involve community and care providers are needed to promote healthy eating for elderly population.